Unjuk kerja furnace menggunakan kawat kanthal A1 - Lubis, Gita Suryani; Sitompul, Otmar Mangara; Herman (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
In the metal heating process, a tool is needed that can help the heat treatment process, namely a furnace where there is a space inside to warm up the workpiece to a certain temperature and hold it for a certain time interval. In this study, the furnace design was carried out using Autodesk Fusion 360 software, while the manufacture of the furnace uses several components such as A1 kanthal wire as a heating element, SK34 refractory brick, and Castabel C16 cement which is used as a heat retaining material. Performance analysis is carried out by calculating the speed of reaching the maximum temperature that can be achieved, the time required to reach the maximum temperature, and energy consumption. Based on the results of design and calculation, a furnace with external dimensions of 40x30x40 cm and heating chamber dimensions of 18x18x18 cm was produced. Furnace trials were carried out by melting aluminium material where the melting point of the material in its pure state is 660oC. Further tests carried out show that the maximum temperature that can be reached is 700oC, while the time required to reach that temperature is 50 minutes with an energy consumption of 2,404.6 Watts.